Enhancing Local Government Accountability through Good Governance Policies: A Mixed-Methods Study - Swastika, Amira Fide; Wibawa, Surya; Metrolitania, Metrolitania; Marvin, Josua; Natalia, Natalia (Institute for Law and Economics Studies, 2024)
This research investigates the implementation of good governance policies and their effect on enhancing accountability within local government systems. Employing a mixed-methods approach, the study combines qualitative interviews, focus groups, document analysis, and quantitative surveys to provide a comprehensive understanding of the relationship between governance practices and accountability outcomes. Key findings indicate that citizen engagement, transparency, and robust legal frameworks are critical components for fostering accountability. The research highlights that active citizen participation significantly correlates with improved accountability perceptions, while transparency measures are essential for building public trust. Additionally, the study identifies corruption and inefficiency as persistent challenges, emphasizing the need for effective anti-corruption strategies and inclusive policies that address socio-economic disparities. By offering practical recommendations for local governments, this research contributes valuable insights to the existing body of knowledge, advocating for a holistic approach that integrates political, legal, and administrative dimensions of accountability.